1988
DOI: 10.1093/infdis/157.5.996
|View full text |Cite
|
Sign up to set email alerts
|

A Nosocomial Outbreak of Branhamella catarrhalis Confirmed by Restriction Endonuclease Analysis

Abstract: An outbreak of respiratory illness due to Branhamella catarrhalis occurred in the intermediate care unit of a Veterans Administration hospital and involved patients and staff members. Four patients had pneumonia and four had bronchitis. Infected patients were placed in a cohort separated from noninfected patients and were treated. Pharyngeal culture was used to survey prevalence in staff and all other patients on the unit; three of 18 staff members and two of 19 asymptomatic patients were positive for B. catar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 21 publications
1
65
0
1
Order By: Relevance
“…catarrhalis is an important nosocomial pathogen has been confirmed by REA on only one occasion to date. 12 We have demonstrated that three of four patients implicated in a suspected outbreak of infection yielded M . catarrhalis strains indistinguishable by the typing methods used.…”
Section: Discussionmentioning
confidence: 89%
“…catarrhalis is an important nosocomial pathogen has been confirmed by REA on only one occasion to date. 12 We have demonstrated that three of four patients implicated in a suspected outbreak of infection yielded M . catarrhalis strains indistinguishable by the typing methods used.…”
Section: Discussionmentioning
confidence: 89%
“…Preliminary observations involving typing of strains indicate that some of the clusters involved infections with several distinct strains of B. catarrhalis (13,121). Other studies implicate person-to-person transmission and suggest that hospital personnel may be involved in transmission (135,144). Analysis of strains from outbreaks by newly developed typing methods will be important in elucidating the factors responsible for nosocomial outbreaks so that rational strategies for prevention can be implemented.…”
Section: Nosocomial Infectionmentioning
confidence: 99%
“…The most widely used method to type strains of B. catarrhalis to date has been restriction endonuclease analysis of genomic DNA (44,45,58,89,118,121,134,135,144). More recently, a more refined form of restriction endonuclease analysis involving pulsed-field gel electrophoresis of large fragments of genomic DNA has been developed (99,102).…”
Section: Genotype-based Typing Systemsmentioning
confidence: 99%
“…1 (5)(6)(7)(8). A typing system suitable for epidemiological surveys of these cases must be readily reproducible, stable, and applicable to the wide range of strains to be typed on the basis of a genetic property (20).…”
Section: Electrophoretic Esterase Typingmentioning
confidence: 99%
“…Nosocomial spread of an outbreak strain of B. catarrhalis has been suggested, but was not confirmed because of the lack of a typing system to establish strain relatedness (5)(6)(7). A recent nosocomial outbreak of respiratory illness due to B. catarrhalis, was confirmed by restriction endonuclease analysis (8). However, electrophoretic typing of esterases has been shown to provide rapid, easy discrimination for epidemiological screening (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%